2014
DOI: 10.1002/jgt.21825
|View full text |Cite
|
Sign up to set email alerts
|

Circumference and Pathwidth of Highly Connected Graphs

Abstract: Birmele [J. Graph Theory, 2003] proved that every graph with circumference t has treewidth at most t − 1. Under the additional assumption of 2-connectivity, such graphs have bounded pathwidth, which is a qualitatively stronger conclusion. Birmele's theorem was extended by Birmele, Bondy and Reed [Combinatorica, 2007] who showed that every graph without k disjoint cycles of length at least t has treewidth O(tk 2 ). Our main result states that, under the additional assumption of (k + 1)-connectivity, such grap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…In addition, F ′ ∩ ε(T w ) is an ε(w)-linked B ν -tree. This proves (7). Now let F be an ε(v)-linked B µ -tree in ε(T v ).…”
Section: Some Preparationmentioning
confidence: 59%
See 3 more Smart Citations
“…In addition, F ′ ∩ ε(T w ) is an ε(w)-linked B ν -tree. This proves (7). Now let F be an ε(v)-linked B µ -tree in ε(T v ).…”
Section: Some Preparationmentioning
confidence: 59%
“…Robertson and Seymour [11] were the first to prove that a graph of large pathwidth contains a subdivision of a binary tree with large height. Marshall and Wood [7] prove an explicit formula if the graph is a tree: Lemma 11 (Marshall and Wood [7], restated). Let T be a tree with at least two vertices.…”
Section: Binary Trees and Pathwidthmentioning
confidence: 99%
See 2 more Smart Citations
“…Nesetril and Ossona de Mendez [NdM12] showed that the pathwidth of a 2-connected graph G is at most (circ(G) − 2) 2 . Marshall and Wood [MW13] improved this bound to circ(G)/2 (circ(G)−1). Generalizing these results to directed pathwidth, under a suitable directed connectivity assumption is an interesting open problem.…”
Section: Introductionmentioning
confidence: 99%